PERBEDAAN PROJECTED MOTION DAN PROJECTED STILL MEDIA TERHADAP KETERAMPILAN MAHASISWA NON-KESEHATAN DALAM MELAKUKAN CARDIOPULMONARY RESUSCITATION - Hasanah, Uswatun; Santoso, Bagus Rahmat; Gaghauna, Eirene E.M (STIKES Suaka Insan, 2023)
Cardiac arrest can lead to brain damage and permanent disability. Many factors can cause cardiac arrest, one of which is due to age. The high mortality rate due to cardiac arrest can be reduced by assisting in the form of Basic Life Support (BLS), namely Cardiopulmonary resuscitation (CPR). People need knowledge in providing CPR. This study aims to determine whether there is a difference between projected motion learning media and projected still media on the skills of non-health students in performing CPR. This study uses a pre-experimental design with a cross-sectional study approach. The population in this study were non-health students of Sari Mulia University, with a sample size of 30 respondents with a quota sampling technique. The instrument in this study used an SOP sheet to perform CPR. Data analysis of this study used a univariate and bivariate analysis, namely the Mann-Whitney test, which showed that the p-value <0.05 (p=0.006), which means there is a difference in the average value of the intervention and control groups. Both groups used the same learning media, which is very suitable to complement the learning experience because it presents realistic learning objects. It was found that projected motion media can increase attention, interaction, and learning motivation to improve students' skills in performing CPR. Keywords: CPR, Skill, Projected motion media, Projected still media